The Impact Of Green Financing On Sustainable Financial Performance: An Applied Study Of A Sample Of Employees In Iraqi Commercial Banks In The Middle Euphrates Region - Iftikhar Jabbar Abed (Harmoni Economics: International Journal of Economics and Accounting, 2024)
The purpose of this study is to show how much green finance—which includes investments in renewable energy, sustainable infrastructure, green technology, social investment, and green bonds—can help a sample of Iraqi bank employees achieve sustainable financial performance, including accounting, marketing, and comprehensive performance. The research problem was that the banking system and the government must work together effectively to provide the required financial tools, such as low-cost bank loans and exemptions from environmental taxes, in order to achieve sustainable financial performance and make the shift to a green economy. By examining the connection between these factors, two primary hypotheses were created to gauge the degree of influence and linkage. The primary instrument for gathering information pertaining to the field component of the study was the questionnaire form. There were 179 people in the sample. The study included a variety of statistical techniques, including standard deviations, arithmetic averages, and structural equation modeling with the aid of statistical tools (spss.var.29, amos.var.26). The most significant of the conclusions drawn was that green financing has a morally beneficial effect on sustainable financial performance.